Profil Mikroskopis Jaringan Hepar Mencit (Mus musculus) yang Difiksasi dengan Neutral Buffered Formalin (NBF 10%) dan Larutan Helly - Melly Agustin (Jaringan Laboratorium Medis, 2021)
The fixation solution that is widely used in anatomical pathology laboratories is NBF 10%, the excess of NBF 10% because the pH is close to neutral, can be stored in large quantities and a long time. Helly's fixation solution is a good fixation solution for the cytoplasm, and only requires 2-3 hours of fixation. Knowing the microscopic picture of the preparation of hepar mencit tissue (Mus musculus) fixated with NBF 10% and Helly solution. This research is an experimental study with a descriptive analysis approach. picture of hepar mencit tissue preparation (Mus musculus) fixation with NBF 10% obtained as much as 100% good preparation. While the fixated with Helly solution obtained as much as 66% good preparation. Conclusion: Microscopic picture of hepar mencit tissue preparation (Mus musculus) fixated with NBF is 10% better than Helly solution.